Managing EYL Students in Learning Vocabulary through Short Islamic Stories - Mastur Thoyib; Dewi Suriyani Djamdjuri; Munadiyah El Haq (STKIP PGRI SITUBONDO, 2023)
The aim of this study is to find out some relevant theories and research relating to managing the EYL students in learning Vocabulary using short Islamic stories. The method used is Systematic Literature Review. The result of the study shows that the use of Islamic short stories offers a comprehensive method of moral and spiritual instruction. These narratives efficiently communicate moral ideals, ethical concepts, and spiritual lessons in an approachable and interesting way by leveraging the power of storytelling. These tales, which are inspired by Islamic history and heritage, encourage cultural sensitivity and a strong sense of Islamic identity. Islamic short stories are a wonderful tool for building good character characteristics and spiritual development because of their capacity to impact hearts and minds. Islamic short stories convey moral quandaries and show the effects of various decisions, making them a valuable resource for moral instruction. Characters that encounter difficulties and make judgments based on Islamic principles like honesty, compassion, and justice are frequently featured in these stories.